THE EFFECT OF GOVERNMENT EXPENDITURE, FOREIGN DIRECT INVESTMENT AND TAX ON ECONOMIC GROWTH IN INDONESIA, MALAYSIA, SINGAPORE AND THAILAND 1999-2018 - Fadilla Hummaira; Fanny Nailufar; Jariah Abubakar (Journal of Malikussaleh Public Economics, 2021)
This study aimed to determine the effects of government spending, foreign direct investment, and tax on the economic growth of Indonesia, Malaysia, Singapore, and Thailand from 1999 to 2018. In this study, the regression analysis used was panel data regression with the model chosen was Common Effect / Pooled Least Square. The results partially show that government spending, foreign direct investment, and tax positively influenced the economic growth in Indonesia, Malaysia, Singapore, and Thailand in 1999- 2018. Simultaneously, government spending, foreign direct investment, and tax positively and significantly influenced the economic growth in Indonesia, Malaysia, Singapore, and Thailand in 1999-2018.